Orientasi Nilai Budaya Banyumas: Antara Masyarakat Tradisional Dan Modern - Sugeng Priyadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2008)
This research aims at finding out the human value of Banyumas people as expressed in Babad Pasir. To achieve this aim, the history method is employed in four steps, (1) heuristic, (2) criticism, (3) interpretation, and (4) historiography. The historical facts which are interpreted are those mental ones so that the resulting historiography reflects Banyumanese ideas as the realization of the Banyumas cultural value system. The results of the research show that Babad Pasir tends to presents internal conflicts, while Babad Banyumas is marked more with ascetism. However, both of them show a paradox between positive and negative values. The relation between the positive values as the thesis and negative ones as the antithesis results in a synthesis in the form of cablaka (straightforwardness) as the value system of the Banyumas culture. Based on the system it can be seen that the orientation of the value is toward both traditional and modern society. Banyumas people tend to look at the past, but have the ability to see the future as a reference in facing the challenging world.